The Computer revolution in public administration : the impact of information technology on government - Pitt, Douglas C.; Smith, Brian C. (Brighton, Sussex : Wheatsheaf Books ; Distributed by Harvester Press, 1984)
Provides an incisive analysis of the impact of the computer revolution upon modern government.
Includes index.
Includes bibliographical references: p. 202-209.
oif 05/08/2016
Loans
Keywords: Administrative agencies; Public administration; Great Britain